THE INFLUENCE OF COMPUTER-BASED INTERACTIVE MEDIA AND STUDENTS' CRITICAL THINKING SKILLS ON LEARNING OUTCOMES OF PHYSICS MATERIAL ELASTICITY OF CLASS XI IPA STUDENTS AT SMA PAKUSARI - Pungkasaningsih sri; Abdul muis (Program Pasca Sarjana, Universias PGRI Argopuro Jember, 2022)
The influence of computer-based interactive media has an influence on critical thinking skills and learning outcomes of physics material Elasticity. Respondents of this study were students of class XI IPA SMAN Pakusari, With a total of 76 students in Class XI IPA 4 with computer-based interactive learning with the MS team application in the 2020 school year, the research area was determined using the purpuse sampling area method. This research is a quantitative research with causal quantitative design. Data collection tools using observation, interviews, documentation and tests. Test Analysis of the instrument using: 1) normality test 2) homogeneity test. Data analysis used multiple linear regression using the product moment. Based on the hypothesis test, it is proven that: (1) the results of the 1-Sample Kolmogorov Smirnov analysis above, obtained the data sig = 0.088. Because the obtained sig > 0.05, then H0 is accepted, Ha is rejected. That is, the experimental class = control class.2). Based on the